Solar and battery input super boost DC–DC converter for solar powered electric vehicle - Yadagiri, Aerpula; Talagadadeevi, Srinivasa Rao; Rao, Seetamraju Venkata Bala Subrahmanyeswara; Rao, Bitra Janardhana; Inthiyaz, Syed; Prakash, Nelaturi Nanda; Rajanna, Bodapati Venkata; Kumar, Cheeli Ashok (Institute of Advanced Engineering and Science, 2025)
The electric vehicle (EV) is increasingly emerging as an attractive solution to reduce reliance on fossil fuels in India. In commercial EVs, solar photovoltaic (PV) technology is employed both to charge the battery and power the vehicle. However, the conventional bidirectional DC-DC converter layout results in underutilization of solar PV power when the battery's state of charge (SOC) reaches maximum capacity. This work offers a unique dual input super boost (DISB) DC-DC converter designed specifically for solar-powered electric vehicles (EVs) to address the aforementioned challenge. The recently suggested converter operates in six different modes to effectively capture solar photovoltaic (PV) power. Notable benefits of this design include a wide range of speed control and fewer conduction devices in each mode, which eventually result in increased overall efficiency. An extensive analysis of the suggested DISB DC-DC converter is carried out by the study, encompassing detailed examination of operating waveforms and dynamic evaluations. Furthermore, the converter's performance and operation under the six different modes are verified through simulation.